Adaptation of powered wheelchairs for quadriplegic patients with reduced strenght - Urbano, Maria Margarida (2012)
This paper discusses the introduction of mechanisms to adapt commercial powered wheelchairs in order to facilitate its driving by quadriplegic people with reduced strength. Several models of operation are proposed and the most promising, at the moment, called legacy adapted mode, is detailed. A part of the formal operation model is presented. The model is then used in the STAGE simulator, not only for its evaluation, but also to tune operational parameters that will be specific of each patient. A brief description of the hardware architecture proposed to adapt the commercial wheelchair will also be included.